(untitled) (Research, Society and Development, 2020)
Rain erosivity discloses the rainfall capacity of a region to generate erosion. The objective is to study the geospatialized variability by generating charts of the monthly and annual rainfall erosivity index considering the equation of soil loss, erosion return time, probability and erosive classification in addition to the rainfall coefficient of the Paraíba River hydrographic basin. Monthly and annual rainfall data for the period 1962-2018 were used. Quantitative research conducted by rainfall data. The use of data was proceeded from analysis with regard to filling in gaps, consistency, homogenization. To estimate the rainfall erosivity index, the methodology suggested by Wischmeier was applied and using Bertoni’s simple equation. It is known that the environmental problems experienced in a certain area interfere in the entire basin, causing direct impacts of silting and degradation. There is a need for prior planning of land for the implantation of orchards and fruitful agricultural projects, so that land displacement does not occur, supported by monitoring the changes that occur in the soil, in hillside regions, considering the level curves of the ground. The arable areas and their surroundings are located throughout its territory, having its climatic regions with different erosive potentials. Therefore, knowledge of this potential will be of enormous value in choosing soil management practices in order to control its erosion process. The completion of this study comes to contribute to regional or local planning and management policies, where it will contribute as a subsidy to new study developments.